Resilience in adolescents with thalassemia - Pattaporn Kaewkong (2020)
© 2020 Taylor & Francis Group, LLC. Adolescents with thalassemia often manifest with an increased risk of emotional and behavioral problems, as well as poor quality of life. However, some can be well-adapted and demonstrate evidence of resilience. This study aimed to explore resilience among those with thalassemia and determine the protective factors for their resilience. Sixty adolescents with thalassemia and 60 healthy adolescents as a comparison group participated in the study. Most adolescents with thalassemia demonstrated resilience. Eighty percent of them scored in the low-risk range of the SDQ total difficulties scale, and 91.7% scored in the low-risk range of the SDQ prosocial scale. The mean total difficulties scores of the thalassemia patients and the healthy controls were 11.38 and 11.27 respectively, whereas the mean prosocial scores were 7.28 and 6.65, without statistical significance. Despite the extensive demands of the illness, most adolescents with thalassemia appear to be adapted well, demonstrating evidence of resilience. Factors promoting resilience are lower BMI, less severe type of thalassemia, and younger age at the start of an iron chelator. Health care professionals who take care of adolescents with thalassemia should collaborate to improve their resilience.